Least cost, utility scale abatement from Australia's NEM (National Electricity Market). Part 2: Scenarios and policy implications. (15th April 2016) - Brear, M.J.; Jeppesen, M.; Chattopadhyay, D.; Manzie, C.; Alpcan, T.; Dargaville, R.
Abstract: This paper is the second of a two part study that considers least cost, greenhouse gas abatement pathways for an electricity system. Part 1 of this study formulated a model for determining these abatement pathways, and applied this model to Australia's NEM (National Electricity Market) for a single reference scenario. Part 2 of this study applies this model to different scenarios and considers the policy implications. These include cases where nuclear power generation and CCS (carbon capture and storage) are implemented in Australia, which is presently not the case, as well as a more detailed examination of how an extended, RPS (renewable portfolio standard) might perform. The effect of future fuel costs and different discount rates are also examined. Several results from this study are thought to be significant. Most importantly, this study suggests that Australia already has utility scale technologies, renewable and non-renewable resources, an electricity market design and an abatement policy that permit continued progress towards deep greenhouse gas abatement in its electricity sector. In particular, a RPS (renewable portfolio standard) appears to be close to optimal as a greenhouse gas abatement policy for Australia's electricity sector for at least the next 10–15 years. Highlights: Considers scenarios and policy implications for Australia's NEM (National Electricity Market). An extended form of RPS (renewable portfolio standard) appears near optimal until roughly 2030. For up to 80% abatement, the inclusion of nuclear achieves only marginal benefit by 2050. CCS (Carbon capture and storage) does not appear competitive with current cost estimates.